Individual Differences in the Association Between Celebrity Worship and Subjective Well-Being: The Moderating Role of Gender and Age - Zsila, Ágnes; Orosz, Gábor; McCutcheon, Lynn E.; Demetrovics, Zsolt (Frontiers in Psychology, 2021)
The association of celebrity worship with mental health concerns has been extensively studied in the past two decades. However, there is a lack of research on basic demographic characteristics that can potentially alter the link between celebrity admiration and different aspects of mental health. The present study investigates the possible moderating role of gender, age and opposite/ same-gender celebrity selection on the association of celebrity worship with general well-being, self-esteem and perceived daytime sleepiness. A total of 1763 Hungarian adults (66.42% men, Mage = 37.2 years, SD = 11.4) completed an online survey focusing on attitudes and behaviors relating to celebrities and mental well-being. The moderation analysis showed that (i) the negative association between celebrity worship and self-esteem was slightly stronger for women than for men, and (ii) the association between celebrity worship and perceived daytime sleepiness was slightly stronger for younger individuals than for older ones. Although both gender and age were particularly weak moderators, these results draw the attention to some potential individual differences when interpreting links between celebrity worship and different aspects of mental health.